Setting the agenda. - Hien, Than Thi (Yemaya : ICSF'S Newsletter on Gender and Fisheries)
A regional conference on women in fisheries held recently in Hanoi, Vietnam defined a regional agenda for the advancement of women and gender equity in fisheries